Penggunaan Gaya Bahasa Jurnalistik Pada Bidang Penyiaran Dan Pemberitaan Di RRI Palembang - Fremia Herawati; Nurseri Hasnah Nasution; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is entitled "The Use of Journalistic Language Style in Broadcasting and News at RRI Palembang". It often happens that broadcasting institutions both government and private have their own problems in news making, news production, and even things that happen during broadcasts. Broadcasting institutions also have their own programs to adjust to the needs of the market and listeners plus the modern era like today in the use of journalistic language styles, few broadcasting or radio institutions apply journalistic language styles properly and correctly. The method used is a qualitative method using Kunjana Rahardi's theory. With the first stage, researchers observed the process of making news in broadcast programs at RRI Palembang and the use of journalistic language styles in the field of broadcasting and news at RRI Palembang. Based on the results of the study, it can be concluded that RRI Palembang will limit the use of journalistic language in broadcasting, from several existing programs that are characterized by contemporary, local language, some even use journalistic language properly and correctly in accordance with the KBBI (Big Indonesian Dictionary) and EYD (Refined Spelling). While in the field of news in making news at RRI Palembang, the field of news in the use of journalistic language styles has followed in accordance with the KBBI and EYD. Which in making news has gone through various processes, standardized sentences, language that is not convoluted and easy to understand. This research is entitled "The Use of Journalistic Language Style in Broadcasting and News at RRI Palembang". It often happens that broadcasting institutions both government and private have their own problems in news making, news production, and even things that happen during broadcasts. Broadcasting institutions also have their own programs to adjust to the needs of the market and listeners plus the modern era like today in the use of journalistic language styles, few broadcasting or radio institutions apply journalistic language styles properly and correctly. The method used is a qualitative method using Kunjana Rahardi's theory. With the first stage, researchers observed the process of making news in broadcast programs at RRI Palembang and the use of journalistic language styles in the field of broadcasting and news at RRI Palembang. Based on the results of the study, it can be concluded that RRI Palembang will limit the use of journalistic language in broadcasting, from several existing programs that are characterized by contemporary, local language, some even use journalistic language properly and correctly in accordance with the KBBI (Big Indonesian Dictionary) and EYD (Refined Spelling). While in the field of news in making news at RRI Palembang, the field of news in the use of journalistic language styles has followed in accordance with the KBBI and EYD. Which in making news has gone through various processes, standardized sentences, language that is not convoluted and easy to understand.